Pendidikan Karakter Sebagai Nilai- Nilai Luhur untuk Membangun Integritas di Sekolah Dasar - Muhamad Arif Alfa Rizi; Idris Hakim Lubis; Ahmad Syarifuddin; Afriza Media; Ari Suriani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to explain the urgency of character education as noble values in shaping individual integrity. The research method used is a literature study, focusing on in-depth analysis of literature reviews, journal articles, and books that discuss the relationship between character education and integrity formation. This research started with the selection of a specific research topic, namely the role of character education in the context of noble values. Furthermore, relevant literature sources were identified and critically analyzed to understand the concept and impact of character education on individual integrity. The results show that character education plays a central role in building the foundation of integrity. Through noble values such as honesty, responsibility, and compassion, individuals can form a solid and responsible personality. The literature study also revealed that the implementation of character education is not only relevant in the context of formal education, but also important in the scope of family and society. The conclusion of this study is the importance of character education as an effective strategy in shaping individual integrity. By detailing key concepts and key findings from the literature, this article provides an in-depth look at how character education, especially those based on noble values, can be a strong foundation in building individuals with high integrity. The implications of this study can provide valuable contributions in the development of character education policies that are more effective and relevant in supporting the formation of an ethical generation.